Representasi Feminisme Dalam Novel Pudarnya Pesona Cleopatra Karya Habiburrahman El Shirazy - Idawati Idawati; Firman Hadiansyah (FKIP, Universitas Palangka Raya, 2023)
Novel Pudarnya Pesona Cleopatra is a story of a portrait of the reality of society's life regarding the female figure. The purpose of this study is to describe the self-image of a female character named Raihana and the representation of feminism contained in the novel Pudarnya Pesona Cleopatra. The research method used is descriptive qualitative method. Data collection techniques with reading and note techniques. The data analysis technique used is content analysis technique. The data validation technique uses data triangulation. The results of the analysis show that Raihana's self-image in the physical aspect is described as a beautiful, elegant, baby face and mature woman. From the psychic aspect, Raihana is described as a figure who is strong, patient, and loves her husband, and obediently worships her God. Individually, Raihana also has the desire to be loved, wanted, and appreciated as a wife. The representation of feminism illustrates that a woman in Javanese culture interprets that women must obey their husband as a leader